FREE RADICAL SCAVENGING AND NEPHROPROTECTIVE ACTIVITY OF BENINCASA HISPIDA (THUNB) LINN. AGAINST GENTAMICIN INDUCED NEPHROTOXICITY IN RATS. - Qadrie, Zulfkar Latief; Rehman, Shakil U; Wafai, Zahoor; Anandan, R.; Ashraf, Humaira; Mushtaque, Md. (Asian Journal of Pharmaceutical Research and Development, 2013)
The seeds of Benincasa hispida (Thunb) COGN. (Family: Cucurbitaceae) was extracted with ethanol and was used to study acute toxicity, nephroprotective effects. Gentamycin was used to induce nephrotoxicity in rats. The extract was non lethal to the rats up to the dose of 5000 mg/kg b.w. At doses of 250 and 500 mg/kg b.w, the extract significantly (P<0.05) increased the nephroprotective effect in a dose dependent manner in rats. Furthermore, the extract was studied for free radical scavenging potential to correlate its nephrprotective activity. These results indicate that ethanolic extract of Benincasa hispida possesses potent nephroprotective effect and thus pharmacologically justifying its folkloric and traditional use in the management of nephrotoxicity conditions (P<0.05) increased the nephroprotective effect in a dose dependent manner in rats. Furthermore, the extract was studied for free radical scavenging potential to correlate its nephrprotective activity. These results indicate that ethanolic extract of Benincasa hispida possesses potent nephroprotective effect and thus pharmacologically justifying its folkloric and traditional use in the management of nephrotoxicity conditions.